864 Methylprednisolone resolved CRP without cardiac sequelae amongst children with PIMS-TS/MIS-C presenting to a UK tertiary centre - Charlesworth, James; Lees, Emily; Navarajasegaran, Joshua; Adwani, Satish; Kelly, Dominic (Archives of disease in childhood, 2023)
ObjectivesPaediatric multisystem inflammatory syndrome associated with COVID-19 (PIMS-TS/MIS-C) remains a novel disease, with phenotypic similarities to Kawasaki disease and concerns that coronary artery aneurysm may develop.1–3 PIMS-TS biomarkers help validate a diagnosis,4 but no markers for disease severity or prognosis exist. This retrospective review of experience in a tertiary centre reports on biomarkers, clinical outcomes and treatment(s) received for PIMS-TS admissions over 2 years.MethodsWe retrospectively reviewed all PIMS-TS admissions (using the RCPCH definition)4 treated in Oxford Children’s Hospital between March 2020 and May 2022. Cases were identified by contemporaneous clinical worklists and clinical coding. Data were extracted and anonymised. Data handled in Microsoft Excel 2013, statistical analysis and representation in GraphPad Prism. Logistic regression, controlling for sex, age and weight centile, compared patients with and without cardiovascular support. Spearman correlation compared continuous variables.ResultsWe identified 64 PIMS-TS admissions, median age 10.3 years (range 1.2–15.2). Where tested, 92.7% were COVID-antibody-positive. Admissions followed peaks in COVID infection regionally (figure 1). N=40 (62.5%) required cardiovascular support with inotropes or vasopressors, which were divided equally across the pandemic (figure 1). Greater peak NT-pro-BNP (median 11,363 versus 3,640 ng/L, p=0.015) and length of stay (median 8.4 versus 6.4 days, p<0.015) were observed amongst those requiring cardiovascular support. Highest CRP (median 201 mg/L), lowest lymphocyte count (median 0.74 x106/L) and lowest vitamin D (median 28 nmol/L) did not vary by cardiovascular support requirement. Vitamin D levels showed a significant inverse correlation with peak CRP (spearman r=-0.34, p=0.007) and time on cardiovascular support (spearman r=-0.34, p=0.030). Furthermore, lowest vitamin D level correlated with lower COVID anti-nucleocapsid titres (spearman r=0.43, p=0.0014). We found IV methylprednisolone treatment (n=53 (82.8%), with n=16 receiving IVIg and methylprednisolone) resulted in a faster resolution of CRP than IVIg alone (n=7, 10.9%) or no immunomodulatory treatment (n=4, 6.2%) (figure 2). No patients had coronary artery aneurysms or cardiac sequelae. The most common cardiac findings were small pericardial effusion (42%), mitral regurgitation and prominent proximal coronaries.ConclusionPatients requiring cardiovascular support had higher NT-Pro-BNP and a greater length of stay. We highlight an association between vitamin D and inflammatory responses, or cardiovascular support, which require further validation. This data supports methylprednisolone treatment without coronary artery aneurysm. Although coronary artery aneurysms have been reported at rates up to 6% in worldwide cohorts,2 unrelated to treatment with IVIg. PIMS-TS remains a challenging, heterogeneous and increasingly rare diagnosis, which this study aims to clarify.ReferencesWhittaker E, Bamford A, Kenny J, et al. Clinical Characteristics of 58 Children With a Pediatric Inflammatory Multisystem Syndrome Temporally Associated With SARS-CoV-2. JAMA 2020;324:259. doi:10.1001/jama.2020.10369McArdle AJ, Vito O, Patel H, et al. Treatment of Multisystem Inflammatory Syndrome in Children. N Engl J Med 2021;385:11–22. doi:10.1056/NEJMoa2102968Sacco K, Castagnoli R, Vakkilainen S, et al. Immunopathological signatures in multisystem inflammatory syndrome in children and pediatric COVID-19. Nat Med 2022;28:1050–62. doi:10.1038/s41591-022-01724-3Harwood R, Allin B, Jones CE, et al. A national consensus management pathway for paediatric inflammatory multisystem syndrome temporally associated with COVID-19 (PIMS-TS): results of a national Delphi process. The Lancet Child & Adolescent Health 2021;5:133–41. doi:10.1016/S2352-4642(20)30304-7Abstract 864 Figure 1